Investigating the library research support services in the Faculty of Education, University of Namibia (UNAM): a Hifikepunye Pohamba Campus focus - Aipinge, Maria Magdalena Muulinawa (Library and Information Studies Centre (LISC), 2020)
This study investigated the library research support services in the Faculty of Education at Hifikepunye Pohamba (HP) Campus, University of Namibia. The research problem is that UNAM has an interest in growing its research, but the library does not have strong research support services; these needed to be investigated, along with researchers’ support needs. The study explored the research support services currently in place at HP campus in order find out to what extent the campus’ library services meet the needs and expectations of the researchers and academic staff. The study further examined how the research support service at the HP campus library could be re-conceptualised. The results of the study aimed at guiding librarians on what research related services should be offered to researchers in order to improve research outputs. The study was guided by the Research Librarianship conceptual approach which provided direction and ideas on an ideal research support service which responds to country, institution and individual research needs and changes in scholarly communication. A mixed methods approach was used to collect and analyse both quantitative and qualitative data. Data was collected using two sampling methods. They are: a census which was conducted for academics and convenience sampling for emerging researchers. Questionnaires were distributed to academic (established researchers) and postgraduate students who are referred as emerging researchers in the study. The findings are that the HP campus library does provide research support services, but they are not really core activities of the research support services as the concept would suggest. Many researchers felt their needs were being met but the current services are not specifically research-related activities and therefore do not help improve on research outputs as much as more targeted research services would. The findings indicated that there is a need to advance the campus’ traditional library services by adding activities which respond to research needs. The study therefore recommended that the library at the HP campus should enhance the research support services by responding to new trends in an academic library which fit into the new higher education teaching environment. Furthermore, the library should develop awareness programmes of the library research support services for academics. It is also recommended that the library should integrate IT skills into library training and that new set of skills such as research and subject-related skills are required by academic librarians. Therefore, staff development should be a continuing programme for UNAM librarians to constantly adapt to new trends and ensure library services are on par with the changes in research. The main recommendation is that the librarians should adapt to new trends and ensure that the library services remain relevant by contributing to research outputs. This will mainly be made possible if librarians have relevant qualifications to enable them to have the competence and skills in research related activities.